Human Rights in Chinese Foreign Relations : Defining and Defending National Interests - Wan, Ming, 1960- (Book collections on Project MUSE., 2001)
"Essential reading for anyone wishing to understand why human rights advocacy has failed in international relations."--Asia and Pacific.